The Clozapine-induced Toxicity via Induction of Oxidative Stress and Mitochondrial Dysfunction in Human Blood Lymphocytes and Protecting role of L-Carnitine: Clozapine-induced Toxicity on Lymphocytes - Pourahmad, Jalal; Salimi, Ahmad; Imani, Farnaz; Jamali, Zhaleh; Ahvar, Negar (International Pharmacy Acta, 2020)
Clozapine is a useful antipsychotic drug but with serious, life threatening toxicity effects. The aim of this study is to assess the direct cytotoxicity effect of clozapine (CLZ) on human blood lymphocytes and investigate the protective effect of L‐carnitine (LC) against clozapine‐induced cytotoxicity. Clozapine at 70 μM concentration induced cytotoxicity following 12 h. The Clozapine induced cytotoxicity was associated with intracellular reactive oxygen species (ROS) generation, mitochondrial membrane potential (MMP) collapse, lysosomal membrane injury, lipid peroxidation, and depletion of glutathione (GSH) and raising of oxidized glutathione (GSSG). We showed that LC (1 mM) has a beneficial cytoprotective effect against clozapine-induced toxicity. Summery, clozapine causes organelles damages and triggers oxidative stress in lymphocytes. These data suggest that using of L‐carnitine could be useful for prevention and treatment of clozapine toxicity. Finally, it could be concluded that LC exerts a beneficial antioxidant and mitochondrial protective effects against oxidative stress induced by CLZ.